2007
DOI: 10.1109/iembs.2007.4352950
|View full text |Cite
|
Sign up to set email alerts
|

Optical dialysis adequacy sensor: wavelength dependence of the ultra violet absorbance in the spent dialysate to the removed solutes

Abstract: A need for dialysate-based, on-line, continuous monitoring systems for the control of dialysis efficiency and the prevention of dialysis-associated complications is arisen due to increasing number of dialysis patients and related treatment quality requirements. The aim of this study was to investigate the wavelength dependence between the the ultra-violet (UV) absorbance in the spent dialysate and the retained solutes removed during the hemodialysis in order to explain possibilities to estimate removal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…There have been many measurements of the UV absorption spectra of uric acid and its anions in aqueous solution, some with specific pH controlled by buffers and some without specified pH values [37,[42][43][44][45][46][47][48][49][50][51][52]. In Supplementary table, we summarize the measurements in order to assess the reliability of calculated vertical excitation energies and present the midrange value for each transition, after rejecting some likely outliers, indicated in italics.…”
Section: Appendices Appendix A-experimental Uv Spectramentioning
confidence: 99%
“…There have been many measurements of the UV absorption spectra of uric acid and its anions in aqueous solution, some with specific pH controlled by buffers and some without specified pH values [37,[42][43][44][45][46][47][48][49][50][51][52]. In Supplementary table, we summarize the measurements in order to assess the reliability of calculated vertical excitation energies and present the midrange value for each transition, after rejecting some likely outliers, indicated in italics.…”
Section: Appendices Appendix A-experimental Uv Spectramentioning
confidence: 99%
“…In [16] authors reported a method for investigating the wavelength dependency between the ultraviolet (UV) absorbance in the spent dialysate and the remaining dissolved salts extracted during hemodialysis to clarify possibility for estimating the optical dialysis suitability sensor for elimination of the dissolved salts. In the North-Estonian Regional Hospital's Department of Dialysis and Urology, 10 uremic patients are diagnosed with 30 hemodialysis therapies.…”
mentioning
confidence: 99%
“…There have been many measurements of the UV absorption spectra of uric acid and its anions in aqueous solution, some with specific pH controlled by buffers and some without specified pH values [37,[42][43][44][45][46][47][48][49][50][51][52]. In Supplementary table, we summarize the measurements in order to assess the reliability of calculated vertical excitation energies and present the midrange value for each transition, after rejecting some likely outliers, indicated in italics.…”
Section: Appendices Appendix A-experimental Uv Spectramentioning
confidence: 99%